Use of computer modeling elements while carrying out laboratory works on general technical disciplines - Теплицький, Олександр Ілліч (Pedagogy of Higher and Secondary Education, 2017)
In the article the technique of carrying out laboratory works on general technical disciplines in higher educational institutions is investigated; the ideas of computer modeling of the phenomena, considered when studying the course «electrical equipment», are revealed.The article analyzes the opportunities of a Microsoft Office package, generalization and computer modeling of physical phenomena in electric circuits.The potential for the use of specialized environments for modeling – the mathematical packages that adapted domains of knowledge for a certain subject –are opened. Universal environments are investigated in detail, they have a common name «Spreadsheets» and encourage effective counting, building of schedules of functional dependences between variables, analyzing and predicting of the behavior of complex physical systems.The paper sets up examples of a statement, that laboratory researches can be used in classes with electrical equipment. The article analyzes the possibilities of process modeling in electric circuits, methods of calculations, the results at these parameters, graphic interpretation of difficult analytical dependences, researches of electric circuit parameters. The technique of carrying out laboratory work on electrical equipment on the subject «Research The Parameters of a Circuit of a Direct Current» is presented by way of illustration.It is proved that the use of computer modeling allows to optimize carrying out of laboratory works, forms cognitive interest and students’ technical abilities in the higher educational institutions.Prospects of further researches are a technique for carrying out laboratory works on general technical disciplines (thermal engineering, machine assembling, hydraulics); using program emulators for process modeling in difficult electric circuits, calculation of paramet ers of the electrotechnology equipment, creation of vector charts and schedules.